Shortage of antiseizure medication in Germany: How big is the problem? - Steidl, Josephine; Krebs, Sabine; Kostev, Karel; Schwab, Stefan; Hamer, Hajo (Epilepsy and Behavior, 2025)
Objectives: We determined the frequency of drug shortages of antiseizure medication (ASM) availability in Germany. Methods: Retrospective and descriptive analysis of databases of 2 pharmaceutical wholesalers in Germany with a market share of about 45% of the German market in July 2023 (chosen arbitrarily) focusing on antiseizure drug shortages (i.e. demand could not be met entirely) and disruptions (i.e. demand could not be met at all) on the level of formulations, ASM and of manufacturers. Results: 98/909 (10.8%) of formulations of ASM with Wholesaler A were listed with drug shortages and 131/872 (15%) of formulations were reported with drug shortages at Wholesaler B. 19 of 222 (8.6%) entire ASM at Wholesaler A and 12/213 (5.6%) of ASM with Wholesaler B were reported with drug shortages. 41/62 (66.1%) manufacturers at wholesaler A and 36/57 (63.2%) manufacturers at wholesaler B reported shortages. The three compounds affected most frequently by drug shortages were pregabalin, levetiracetam and carbamazepine. 1.7% (Wholesaler A) and 12.9% (Wholesaler B) of formulations were listed with disruptions. 16.7% (40/239) of ASM with drug shortages/disruptions were brand-name ASM and 83.3% (199/239) were generic ASM. Conclusions: 11% to 15% of ASM formulations had drug shortages in Germany in July 2023. Generic ASM were more frequently affected than brand-name ASM. About 2/3 of manufacturers were reported to have drug shortages.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Antiseizure medication; Drug shortages; Epilepsy